Effects of different irrigation regimes in physico-chemical properties of dentin and consequences of changes in the adhesion of microorganisms and AH Plus sealer - Tartari, Talita (2017)
Besides of the desired effects, the chemical solutions used to assist the endodontic instruments in the cleanliness and disinfection of the root canal system can also cause changes in the physicochemical properties of dentin, and consequently affect the adhesion of endodontic sealers and microorganisms to the root canal walls. However, the effects of new irrigators and irrigation protocols remain unknown. The objectives of this thesis were to verify the alterations in the properties of some irrigants when used combined in mixtures, to define the time necessary for the smear layer removal by a new irrigant, to determine the organic matter dissolution capacity and the effects in the physicochemical properties of dentin of some irrigation solutions and protocols, and to evaluate the adhesion of microorganisms and AH Plus sealer to dentin after its submission to different irrigation sequences. In all experiments with dentin, the samples used were obtained from bovine teeth. In the analysis performed in this thesis, the following solutions were tested isolated and combined in different irrigation protocols: saline solution (control), sodium hypochlorite (NaOCl), trisodium (EDTAHNa3), alkaline ethylenediaminetetraacetic acid tetrasodium (EDTANa4), chlorhexidine (CHX), peracetic acid (PAA), and etidronic acid (HEDP). The EDTAHNa3 and EDTANa4 were tested in relation to their effects on the free chlorine content of NaOCl. The solutions were mixed in a 1:1 ratio and the iodometric titration of the mixtures performed in different time intervals. The time necessary for smear layer removal from dentin samples by solutions of EDTAHNa3 and different concentrations of EDTANa4 isolated and mixed with NaOCl was determined with the aid of the scanning electron microscope (SEM). The capacity of NaOCl to dissolve organic matter was determined by weighting fragments of bovine muscle before and after immersion in solutions of 1%, 2.5%, and 5% of NaOCl in different periods of time. Also, the effects of EDTAHNa3, EDTANa4 and HEDP on the organic matter dissolution by NaOCl were evaluated. The alterations produced by all solutions isolated and some irrigation protocols in the organic and inorganic components of the dentin surface were analysed by the attenuated total reflectance of Fourier transform infrared spectroscopy (ATR-FTIR) technique. Absorbance spectra were collected from the dentin surface before and after immersion of samples in the irrigants and the ratios of the amide III/phosphate and carbonate/phosphate bands were calculated. To quantify the adhesion of CHX to mineralized dentin and to dentin demineralized by different irrigation protocols, the areas of the band associated with CHX with the peak in 1492 cm1 were determined in spectra obtained by ATR-FTIR. The effects of different irrigation protocols in the roughness and wettability of dentin surface were measured with a benchtop roughness tester and the sessile drop technique, respectively. For the assays of microorganisms adhesion, samples were prepared and treated the same way and with the same irrigation protocols used in the roughness and wettability tests. Following, Candida albicans and Enterococcus faecalis were maintained in contact with the dentin for 2 hours and the samples were analyzed on the confocal laser scanning microscope (CLSM). Tests of push-out were performed to determine the impact of different irrigation protocols on the dentin bonding strength of AH Plus sealer over time. Canals of bovine incisors teeth were instrumented, irrigated and following obturated using only the sealer AH Plus. Half of the samples were submitted to pushout assessment 7 days after the obturation and the other half 20 months later. The results of the experiments showed that the EDTAHNa3 caused an almost complete and immediate loss of free available chlorine from NaOCl, whilst EDTANa4 promoted a slow and concentration-dependent decline. The smear layer was removed only by decalcifying solutions and in about 1 min by the 17% EDTAHNa3 and 5 min by the EDTANa4, both isolated or mixed with NaOCl. The increase in NaOCl concentration and contact time with the samples intensified the dissolution of organic matter. The mixtures of NaOCl with EDTANa4 and HEDP were able to dissolve the fragments of bovine muscle over-time, however, the EDTAHNa3 strongly affected the NaOCl dissolution capacity when they were mixed. The results of ATR-FTIR experiments showed that the increase in the NaOCl concentration intensified the deproteination of the dentin collagen with a reduction in the amide III/phosphate ratio. For the same decalcifying agent, the higher the concentration and immersion time the greater the removal of phosphate, exposure of the collagen matrix and consequently the increases in amide III/phosphate ratio. The PAA caused greater increases in amide III/phosphate ratio, followed by EDTAHNa3, EDTANa4 and HEDP and this order was maintained in the protocols in which NaOCl was used before the decalcifying agents. NaOCl required approximately 0.5 min to deproteinate the collagen matrix exposed after phosphate removal by EDTAHNa3 and PAA. The carbonate/phosphate ratio decreased after 30 s of samples immersion in solutions of NaOCl at 1%, 2.5% and 5% with no more alterations over time. The carbonate of the dentine was removed faster than phosphate by all decalcifying agents employed alone and in the irrigation protocols in which the use of the NaOCl was followed by the use of the EDTAHNa3, PAA and HEDP. For irrigation protocols that associate NaOCl with chelating solutions, the last irrigant used defined the final dentine amide III/phosphate and carbonate/phosphate ratios. For the ATR-FTIR analysis of CHX adhesion, the results showed that the adsorption of this irrigant to the dentin was potentiated when chelating agents were used prior to the CHX. In relation to the experiments of surface roughness, the saline solution, NaOCl, HEDP and CHX did not alter the roughness of the dentin, but EDTAHNa3 and PAA increased it. The wettability of the surface increased after the use of all irrigants, being the HEDP to cause the greater increases. In the assays of microorganisms adhesion, the smear layer and collagen exposed by the chelating agents favored the adhesion of E. faecalis. The C. albicans adhesion was major in surfaces with smear layer and more mineral. The use of CHX as the final irrigant reduced the adhesion of both microorganisms. The wettability did not influence the microorganisms adhesion, while increases in roughness seems to potentiate the adherence of E. faecalis. The experiments of bond strength of AH Plus to the dentin showed that the irrigation with NaOCl and mixture of NaOCl + EDTANa4 produced the lowest push-out bond strength values in 7 days compared to NaOCl + EDTAHNa3, NaOCl + EDTAHNa3 + NaOCl, NaOCl + EDTAHNa3 + CHX and the mixture of NaOCl + HEDP. After 20 months the lowest values were obtained in the groups irrigated with NaOCl and NaOCl + EDTAHNa3. The groups of NaOCl + EDTAHNa3 + NaOCl, mixture NaOCl + HEDP, and mixture NaOCl + EDTANa4 presented values of push-out bond strength in 20 months similar to the values in 7 days. It was possible to conclude that the irrigation solutions tested in this study have different effects in the organic and inorganic matter and some of them can affect the action of each other when mixed. Independent of being used isolated or combined in irrigation protocols, these irrigants cause modifications in the dentin physicochemical properties that influence the adhesion of AH Plus sealer in short and long term and the microorganisms adherence to thesurface in cases of recontaminations.